도덕 수업에서의 초학문적 융합 수업 실행 - 김영은; Kim Young-eun (윤리연구, 1(124), 2019)
본 연구는 실생활 맥락에서 교과 간, 교과를 가로지르는, 교과를 초월한 학습을 강조한 초학문적 융합 패러다임에 주목하고 있다. 이 패러다임은 21세기 역량을 위한 삶과 배움의 통합 및 유의미성과 관련이 깊다. 본 연구는 21세기 역량을 실현하기 위해 도덕과 수업에 초학문적 융합 패러다임을 도입하여 실천한 사례를 담고 있다. 두 학교의 중학교 1학년 수업에서 “복잡한 문제, 실생활 맥락, 학생 주도, 지식 생산, 행동 및 체험”이라는 수업 원리에 따라 설계한 초학문적 융합 프로그램의 실행 과정에서 드러난 교사의 내러티브와 학생 반응을 담고 있다. 학생 역량 강화를 위한 초학문적 융합수업의 도덕과 현장 실행 결과를 제시하고 도덕과에 주는 시사점을 도출하였다. This study pays attention to Transdisciplinary Learning paradigm which emphasizes learning between, across, and beyond subject disciplines on the context of real life. This paradigm is deeply related to the relevance and meaningfulness of learning and life for the 21st century skills. This study is a kind of action research that two moral subject teachers practice transdisciplinary learning programs to strengthen 21st century competencies through moral subject education for the middle school first graders. This study shows the teachers’ narratives and students’ responses revealing in the execution process of programs which are designed by TRANS learning principles such as “Tangled problems, Real life context, Action-oriented, kNowledge-production, Student-empowered.” Then, the results of transdisciplinary learning applied to moral subject education are presented and implications for moral subject education are drawn.